2023
DOI: 10.1002/fft2.306
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect and mechanism of mangiferin on D‐galactose‐induced oxidative stress and cognitive impairment in aging mice by an integrated network pharmacology and experimental validation strategy

Jing Zhang,
Yanmei Chen,
Zhengxuan Wang
et al.

Abstract: Mangiferin (MAN) was a natural bioactive xanthone with remarkable antioxidative, anti‐inflammatory, and antiapoptotic effects. The purpose of this study to determine the protective influence of MAN on D‐galactose (D‐gal)‐induced aging and cognitive impairment, together with its underlying molecular mechanism. The network pharmacology molecular docking analysis revealed that MAN has a potential binding with aging‐related oxidative stress and apoptosis proteins. In D‐gal‐induced aging mice, MAN could significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 66 publications
(71 reference statements)
0
1
0
Order By: Relevance
“…Many studies have reported that natural products from Anneslea fragrans , Anthurium schlechtendalii Kunth , Mango, etc. had protective effects on the liver, kidneys, and brain via the regulation of these biomarkers [ 49 , 50 , 51 ]. Our results also revealed that QE treatment could significantly decrease the plasma activities of ALT and AST, the BUN level in the kidney, and the AchE activity in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that natural products from Anneslea fragrans , Anthurium schlechtendalii Kunth , Mango, etc. had protective effects on the liver, kidneys, and brain via the regulation of these biomarkers [ 49 , 50 , 51 ]. Our results also revealed that QE treatment could significantly decrease the plasma activities of ALT and AST, the BUN level in the kidney, and the AchE activity in the brain.…”
Section: Discussionmentioning
confidence: 99%